1992
DOI: 10.1161/01.str.23.12.1705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of carotid atherosclerosis in a general population.

Abstract: Background and Purpose: The aim of this study was to assess the prevalence of asymptomatic carotid atherosclerotic lesions and their relation to principal risk factors. The importance of the relation between asymptomatic carotid atherosclerotic lesions, stroke, and coronary atherosclerosis has been widely discussed, but there are few transversal and longitudinal studies on a general population.Methods: A noninvasive examination was carried out using high-resolution B-mode ultrasonography, which has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
3
32

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(194 citation statements)
references
References 49 publications
13
146
3
32
Order By: Relevance
“…Jungquist et al 14 found stenosis of 60% or greater in 4.5% of men aged 69 examined in his study. Prati et al 12 reported a very low prevalence of stenotic plaque (>40%) in subjects aged 80 years or older (7.1% in men and 12.1% in women). These data, derived from cross-sectional studies, do not allow speculation as to the natural history of atherosclerotic disease in elderly subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Jungquist et al 14 found stenosis of 60% or greater in 4.5% of men aged 69 examined in his study. Prati et al 12 reported a very low prevalence of stenotic plaque (>40%) in subjects aged 80 years or older (7.1% in men and 12.1% in women). These data, derived from cross-sectional studies, do not allow speculation as to the natural history of atherosclerotic disease in elderly subjects.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 any vascular bed (Table 1). 6,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Progression of carotid atherosclerosis also is influenced by concomitant risk factors (Table 2). [31][32][33][34][35][36][37] Carotid atherosclerosis is commonly found in association with coronary and peripheral atherosclerosis.…”
Section: Methodsmentioning
confidence: 99%
“…27 This can be explained by the fact that at older age, BMI is not such an important determinant of common CIMT. Several studies [37][38][39][40][41] showed that in middle-aged and elderly subjects, only age, hypertension, dyslipidemia and current smoking were important independent determinants of increased common CIMT. In these studies, the association between BMI and CIMT was probably mediated through a number of these risk factors and lost its significance when adjusted for them.…”
Section: Change In Body Mass Index and Increased Cimt A Oren Et Almentioning
confidence: 99%